Avaliação da eficácia de novos extratos vegetais anestésicos e da tricaína para juvenis de tambaqui colossoma macropomum (cuvier, 1818): implicações sobre as respostas de estresse - BARBAS, Luis André Luz (2015)
This study aimed to evaluate the efficacy of the essential oil (EO) of Nectandra grandiflora Nees, extract of Spilanthes acmella var oleracea obtained through supercritical fluid extraction methodology with the use of CO2 and tricaine (MS-222) as anaesthetics for juvenile tambaqui Colossoma macropomum (Cuvier, 1818), as well as their impact on physiological balance and oxidative stress after deep anaesthesia and transport with sedation. Fish (3.3 to 65.74 g) were acclimated for 15 days in recirculation systems with daily partial changes of water. Water quality parameters were controlled and adequately maintained for the species. At least five concentrations of S. acmella extract, EO of N. grandiflora and tricaine were tested and concentrations ranges were determined in preliminary tests. The dosage of 20 mg of L-1 of extract of S. acmella was enough to promote fast (induction time within 3 min) and deep anaesthesia in juvenile tambaqui (46.6 g), which were also evaluated for secondary stress responses post-anaesthesia during 72 hours in recovery. Transient physiological changes occurred mainly between 2 and 24 h post-anaesthesia with S. acmella extract and variabl returned to normal values after 72 h in recovery, except for the lower concentration of blood Na+ which did not return to normal levels compared to reference values of non18 anaesthetized fish. Tricaine efficiently induced fast and deep anaesthesia at 240 mg L-1 and forward and no clear advantages were observed with the use tricaine in transports for up to 10 h at the sedation concentration of 20 mg L-1 for the mitigation of oxidative stress. The EO N. grandiflora required at least 200 μL L-1 to promote deep anaesthesia, however, fast induction was not achieved. The extract of S. acmella at 10 mg L-1 was sufficient to promote fast and deep anaesthesia in juveniles (3.3 g) subjected to the anaesthetic baths. After transport for 2, 6 and 10 h in the presence or absence of EO of 25 N. grandiflora and extract of S. acmella (30 μL L-1 L and 1 mg L-1, respectively) tissues 26 (muscle, liver, brain and gills) were collected and evaluated for oxidative stress responses throught the indicators: total antioxidant capacity (ACAP), GST activity and thiobarbituric acid reactive substances (TBARS). These concentrations of EO N. grandiflora and extract of S. acmella were effective in protecting tissues against oxidative damage mainly in muscle and gills of transported fish. Juvenile transported for 2, 6 and 10 h in the presence of S. acmella extract (1 mg L-1) and tricaine (20 mg L- 1) showed no significant changes in secondary stress responses in blood compared to animals transported without anaesthetics, whereas the EO of N. grandiflora at the concentration of 30 mg L-1 restrained these responses mainly by decreasing or maintaining normal blood glucose levels and maintaining normal concentrations of Na+ in blood after transport. All anaesthetics used in this study were effective and safe to promote deep anaesthesia and uneventful recovery in tambaqui. Sedation concentrations of the extracts of N. grandiflora and S. acmella are therefore recommended for juvenile tambaqui transported in plastic bags for up to 10 h since secondary stress responseswere attenuated and lipoperoxidation process in tissues was reduced by the presence thereof.